Wind Power Generation for Isolated Loads with IoT-based Smart Load Controller - Chatterjee, Arunava (Peneliti Teknologi Teknik Indonesia, 2024)
This study presents an investigation of combining a microgrid structure for the generation of power with a wind energy conversion system. The chief purpose of the study is to provide a smart controller for such a hybrid system with a dump load for controlling the generated voltage. The smart load controller is used which is unique and it is controlled using Internet-of-Things (IoT) for easier and flexible control. Only the dump load is controlled using the IoT-based controller in a way to keeps the bus voltage at a steady value. With the proposed control, the load voltage regulation becomes better with reduced transients. The generation system can be modeled and installed in any isolated place with optimized use of renewable sources with stable power output. Simulations and experimental observations on a laboratory setup for load control authenticate the proposed method.